BEST PRACTICES IN CSR PROGRAMS: EMPOWERMENT OF URBAN HOME INDUSTRY ENVIRONMENTAL SUSTAINABILITY - Aziz, Abdul; Mufarika, Rully (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2024)
The concept of an urban village aligns with the sustainability development framework by enhancing urban civilization and socioeconomic culture. However, inadequate environmental management has led to problems, such as irresponsible household industries and small and medium enterprises exacerbating socio-environmental issues through poor waste management and unsanitary food production practices. The presence of companies plays a crucial role in community development through Corporate Social Responsibility (CSR) programs. An example is the